Correlation between the diameter of esophageal varices measured using a virtual ruler under endoscopy and portal pressure gradient - Mao, Yudi; Fang, Zhongliang; He, Yingying; Jin, Jing; Ding, Xiping; Kong, Derun (Frontiers in Medicine, 2024)
Background: Esophageal variceal diameter (EVD) is a crucial factor in determining the risk of esophageal variceal bleeding, which arises from an increased portal pressure gradient (PPG). However, research on the relationship between EVD and PPG has been limited, primarily because the assessment of EVD depends on visual estimation during endoscopy. Recently, we developed a method utilizing artificial intelligence (AI) to detect EVD. In this study, we aim to investigate the correlation between EVD and PPG, with the objective of evaluating the potential of using EVD to assess PPG.Comprising retrospective and prospective data, a total of 128 patients with portal hypertension and gastroesophageal varices from two medical institutions were included in this study. Clinical information including PPG, biochemical markers and blood routine was collected. Retrospectively, EVD was evaluated using an AI-based virtual ruler In the prospective phase, the measurement of PPG was conducted through radiation intervention methods, and EVD was measured during endoscopy with the aid of AI.Results: A positive correlation between PPG and EVD (r=0.521, P<0.001) was identified, which was further corroborated by multivariate linear regression analysis (b=6.521, t=6.872, P<0.001). Upon dividing the data into two groups based on PPG levels, (27 cases with PPG<20mmHg and 101 cases with PPG≥20mmHg group), a significant difference in EVD was observed between the groups (OR=29.275, 95% CI 5.590-153.404, P<0.001), with larger EVD in the higher PPG group. These findings suggest that EVD could serve as a predictor of adverse events associated with elevated PPG levels. In addition, the ROC curve analysis indicated that EVD had an accuracy of 0.814 in diagnosing PPG function (Standard error 0.048, 95% CI 0.720-0.908; P<0.001), suggesting that PPG levels might exceed 20mmHg when the variceal diameter surpassed 1.1 cm.EVD exhibited a positively association with PPG and could potentially predict and assess PPG levels, offering novel insights for non-invasive detection of PPG.